Analisis dampak Bank Sampah Wangun di Desa Batukuwung, Kecamatan Padarincang terhadap kesejahteraan masyarakat dan lingkungan - Utari, Enggar; Yanti, Dini Khanifa; Amelia, Lisa; Humairoh, Mamai (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Waste is a major problem throughout Indonesia. One example of waste management is the waste bank. The waste bank is an institution for managing waste effectively, with community involvement. This research applies descriptive and quantitative methods. The research aims to determine the impact of the Wangun Waste Bank on the welfare of the community and the environment in Batukuwung Village, Padarincang District, Serang Regency, Banten Province. The existence of a waste bank in Batukuwung Village has a good impact on people's welfare because it can increase people's income, so that it can help the community's economy. Apart from that, the existence of this waste bank can reduce the number of unemployed people because some people become waste bank managers. With reduced piles of waste the source of disease is also reduced. In general, waste banks have a lot of positive impressions on the surrounding environment and people's welfare.